Expressed Demand for Health Care Services in Regional South Australia: A Cross‐sectional Study. Issue 3 (30th June 2020) - Leach, Matthew J.; Walsh, Sandra; Muyambi, Kuda; Gillam, Marianne; Jones, Martin
Abstract: Purpose: Accessibility and availability of health care services/providers is an increasing concern for many regional communities, particularly regional South Australia. Assessing the level of health service/provider utilization within a region (ie, expressed demand) can be useful in determining health care need and health service/workforce demand. Methods: The regional South Australia health (RESONATE) survey aimed to determine the expressed demand for health care services and the health workforce in a regional South Australian population. The study was open to adults living in regional South Australia and was promoted using a comprehensive multimodal recruitment campaign. Data were collected between April 2017 and March 2018 using the consumer utilization, expectations and experiences of healthcare instrument. Findings: A total of 3, 926 adults completed the questionnaire. Participants reported using 47 different health care providers in the previous 12 months. Whilst almost all (92.9%) participants had seen a general practitioner in the past 12 months, yoga instructors, chiropractors, pharmacists, and physiotherapists were visited most frequently. Proportionally fewer participants in more remote locations received conventional services/treatments, though a significantly greater proportion of those in more remote locations had received complementary medicine services/treatments (relative to inner regional areas). Conclusions: Findings of the RESONATE survey point to a high level of expressed demand for conventional and complementary health care services among study participants, possibly higher than that reported in the general population. Examining the extent to which the health needs of this and other regional populations are met should be the focus of further research to better inform future health workforce/services planning.